Digital Literacy as a Mediator Between Financial Literacy and Investment Scam Awareness - Mithila, G.; Kengatharan, L.; Sinthujakanna, V. (University of Sri Jayewardenepura, 2026)
The rapid expansion of digital financial services in developing economies has increased young adults’ exposure to online investment scams, while financial and digital capabilities have not progressed at the same pace. Although financial literacy is widely recognised as a protective factor against fraud, limited research examines whether digital literacy enables individuals to translate financial knowledge into effective scam awareness, particularly in frontier market contexts. Guided by Protection Motivation Theory, this study investigates the mediating role of digital literacy in the relationship between financial literacy and investment scam awareness among undergraduates in Sri Lanka. Using a stratified random sample method, data is collected from three hundred and ninety-six undergraduates. Partial least squares structural equation modelling is employed to examine the roles of budgeting skills, financial attitudes, product knowledge and risk awareness, conceptualised as dimensions of financial literacy, in predicting investment scam awareness, with digital literacy as a mediating variable. Findings indicate that budgeting skills, financial product literacy and risk awareness positively influence digital literacy, whereas financial attitude shows no significant effect. Digital literacy exerts a strong positive influence on scam awareness. Mediation analysis further reveals that digital literacy significantly mediates the effects of budgeting skills, product literacy and risk awareness on scam awareness, but does not mediate the influence of financial attitude. The evidence suggests that digital competence plays an important role in translating financial literacy into practical vigilance against investment fraud. The study highlights the need for integrated financial and digital literacy interventions to prevent scams. Also, the results imply that financial education programs in developing countries should integrate digital competence training to strengthen consumer resilience to online financial deception.
Keywords: Financial literacy; Digital literacy; Investment scams; Behavioural finance; Developing economies